Parental Reports of Oral Health Behaviours and Dental Caries in Romanian Children and Adolescents: A Cross-Sectional Study - Darius Dacian Macavei; Raluca Iurcov; Abel Emanuel Moca; Rebeca Daniela Marton; Gabriela Ciavoi; Ligia Luminița Vaida (Children, 2026)
Background/Objectives: Dental caries remains one of the most prevalent chronic diseases in childhood, influenced by a combination of hygiene, dietary, and access-related behaviours that are largely shaped by parental involvement. This study aimed to evaluate oral hygiene habits, dietary risk factors, access to dental services, awareness of caries prevention, and the impact of oral health on the child, in relation to parent-reported dental caries in Romanian children and adolescents. Methods: A cross-sectional study was conducted using a structured online questionnaire completed by parents or legal guardians of 508 children and adolescents aged under 18 years. Associations between categorical variables and reported caries were assessed using chi-square tests and Cramér’s V. Ordinal variables were compared using the Mann–Whitney U test. A multivariable logistic regression identified independent predictors of reported caries, with robustness examined through sensitivity analyses. Results: Parent-reported caries was present in 61.2% of children. The strongest associations with caries were the absence of parental supervision during brushing (Cramér’s V = 0.364), the age at which children began brushing unsupervised (V = 0.354), and the reason for the last dental visit (V = 0.426). In the multivariable model, older age, absence of brushing supervision, sweets before bedtime, less frequent dental visits, and rural residence were independent predictors (all p < 0.05; Nagelkerke R2 = 0.361). All six assessed dimensions of oral-health impact on the child were significantly associated with caries, with physical discomfort showing the largest effect (V = 0.349). Conclusions: Parent-reported caries risk in this population clustered around a small number of modifiable behaviours rather than any single dominant factor, while reported caries was associated with a substantial burden on children’s daily functioning. These findings point to sustained parental supervision and routine, non-symptomatic dental care as priority targets for future prevention efforts, although intervention studies are needed to confirm their effectiveness.